Labeling of apoptotic JURL-MK1 cells by fluorescent caspase-3 inhibitor FAM-DEVD-fmk occurs mainly at site(s) different from caspase-3 active site - Kuzelová, Katerina; Grebenová, Dana; Hrkal, Zbynek (Cytometry. Part A, 2007)
BACKGROUND: Fluorochrome-labeled inhibitors of caspases (FLICA) have been designed as an alternative tool for the detection of caspase activation in whole cells. They should label the active site of the corresponding caspase through a covalent attachment to the reactive cysteine residue. METHODS: One of the FLICAs, FAM-DEVD-fmk, was used to monitor apoptosis progression in leukemic JURL-MK1 cells by means of flow cytometry. The effects of unlabeled caspase inhibitors z-DEVD-fmk and z-VAD-fmk on FLICA staining were analyzed to evaluate the contribution of caspase-bound FLICA to the fluorescent signal. Covalent binding of inhibitors to caspase-3 subunit was revealed by Western blotting. RESULTS: Although the unlabeled inhibitors irreversibly bind to caspase-3, completely inhibit its activity, and prevent FLICA binding to caspase-3 even at concentrations lower than 5 muM, they have no effect on FLICA staining of apoptotic cells. CONCLUSIONS: Fluorescent signal of FLICA is characteristic for apoptotic cells but originates mainly from yet unspecified site(s) that differ from the caspase active site. This finding puts in doubt the specificity of staining by various FLICAs with regard to individual caspases and shows the need for an extreme care in the interpretation of data obtained using these labels.
Keywords: Sensitivity and Specificity; senzitivita a specificita; Humans; Substrate Specificity; podjednotky proteinů; vazebná místa; lidé; Protein Processing, Post-Translational; Binding Sites; posttranslační úpravy proteinů; barvení a značení; chloromethylketony aminokyselin; reprodukovatelnost výsledků; apoptóza; inhibitory kaspas; Kinetics; fluorescenční barviva; Fluorescent Dyes; Flow Cytometry; Propidium; kinetika; Reproducibility of Results; substrátová specifita; Amino Acid Chloromethyl Ketones; propidium; Protein Subunits; nádorové buněčné linie; průtoková cytometrie; Cell Line, Tumor; Caspase Inhibitors; Staining and Labeling; Apoptosis